2003
DOI: 10.1177/000348940311200315
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Radiofrequency Volumetric Tissue Reduction of the Palate for Snoring

Abstract: To assess the long-term efficacy and morbidity of radiofrequency volumetric tissue reduction (RFVTR) of the soft palate for snoring, we examined the medical records of 39 patients who received this treatment at an academic medical center. Telephone interviews were conducted with the patients to evaluate the long-term subjective efficacy and sequelae. The average follow-up was 14 months (range, 3 to 26 months). Twenty-eight patients (72%) responded to treatment, defined as a 4-point decrease on a 10-point scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 9 publications
1
25
0
2
Order By: Relevance
“…After a mean follow‐up period of 14 months, 41% of their patients demonstrated a relapse of snoring. Said et al reported a relapse of snoring in 11% of their initial responders 14 months after treatment 12. Two studies from Helsinki re‐evaluated initial success rates (3 months) after 12 and 9.5 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After a mean follow‐up period of 14 months, 41% of their patients demonstrated a relapse of snoring. Said et al reported a relapse of snoring in 11% of their initial responders 14 months after treatment 12. Two studies from Helsinki re‐evaluated initial success rates (3 months) after 12 and 9.5 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Only limited data is available concerning long‐term effects of soft palate procedures in general, and RF surgery in particular. In the trials available, a relapse of snoring was seen as snoring scores of some of the patients increased compared to the results at short term follow‐up 9–12…”
Section: Introductionmentioning
confidence: 99%
“…Apart from conservative treatment options, many different surgical procedures are offered such as laser-assisted uvuloplasty [10], uvulopalatopharyngoplasty [7,8] or radiofrequency surgery [14][15][16][17][18][19]. Initially, radiofrequency surgery of the soft palate seemed to be promising in the treatment of primary snoring, most recent results of a placebo-controlled study however showed that the reduction of snoring scores that may be achieved is only moderate [19].…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous approaches to find an adequate surgical treatment for primary snoring, no gold standard exists. Various kinds of surgical procedures are available, most of which have been developed for the treatment of obstructive sleep apnea (OSA): uvulopalatopharyngoplasty [7,8], tonsillectomy [9], laser-assisted uvulopalatoplasty [10], uvulaflap [11,12], soft palate implants [13], or radiofrequency surgery of the tongue base or the soft palate [14][15][16][17][18][19]. Some of these procedures are rather invasive and connected with side effects such as post-operative pain or bleeding or persistent swallowing difficulties [20], whereas others show only moderate efficacy [19].…”
Section: Introductionmentioning
confidence: 99%
“…The immediate result is contraction of collagen fibers, with subsequent healing and remodeling processes that cause shortening of the fibers and tightening of the tissue [22]. This specific effect of RF energy has been applied for treating gastroesophageal reflux disease (GERD) [23][24][25], benign prostatic hypertrophy [26], joint capsule instability [27], and even obstructive sleep apnea syndrome and snoring [28][29][30]. Temperature-controlled RF is a modification of the technology in which a constant temperature monitoring and feedback is used to control the amount of energy delivered to the treated tissue, with a simultaneous cooling that minimizes the damage to the surface.…”
Section: Radiofrequencymentioning
confidence: 99%